2014
DOI: 10.1590/1982-0216201410613
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome de tensão musculoesquelética, musculatura laríngea extrínseca e postura corporal: considerações teóricas

Abstract: O tema deste estudo é a Síndrome de tensão musculoesquelética, musculatura laríngea extrínseca e postura corporal. Tem como objetivo descrever, a partir de revisão de literatura,as características da musculatura extrínseca da laringe; postura corporal; Síndrome de tensão musculoesquelética e suas implicações vocais; avaliação e tratamento fisioterapêutico e fonoaudiológico. Foi realizado levantamento bibliográfico dos últimos 13 anos em que foram incluídos artigos cujo objetivo e/ou corpo do texto estivessem e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 32 publications
0
11
0
1
Order By: Relevance
“…The vocal hyperfunction or hypertension is one of the main features of the functional and organofunctional dysphonia, it generates increased tension in the laryngeal muscles and also affects external muscles 3,4,8,9 . Overall, the loss in vocal production is related to inadequate respiratory function, misuse of sounding boards, hypertension lingual, laryngeal and perilaryngeal and cervical muscles 6,19,20 . In such cases, they are common the presence of edema or nodules, glottal gaps and high larynx, and these features more commonly found in women [15][16][17] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The vocal hyperfunction or hypertension is one of the main features of the functional and organofunctional dysphonia, it generates increased tension in the laryngeal muscles and also affects external muscles 3,4,8,9 . Overall, the loss in vocal production is related to inadequate respiratory function, misuse of sounding boards, hypertension lingual, laryngeal and perilaryngeal and cervical muscles 6,19,20 . In such cases, they are common the presence of edema or nodules, glottal gaps and high larynx, and these features more commonly found in women [15][16][17] .…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the work of guidance on the postural adaptation, associated with the nasal sound, that is also relaxing to be offered subject to improvement in blood pressure and body balance, it also helps to release tension of the vocal apparatus, the cervical muscles and waist scapular. Disharmony posture generally is related to the vocal change of hyperfunctional purpose and it can be related to the vocal change as a result of imbalances in the craniocervical muscles 3,4,6,8,9,19,21 . Thus, upright posture allows greater freedom of vertical movements of the larynx and avoids the tension of cervical muscles and shoulder girdle, improving vocal production as a whole 3,4,[6][7][8]9,21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This hyperfunctional musculature pattern leads to abnormal larynx elevation in the neck and greater participation of the extrinsic musculature during phonation [4], which causes increased force or tension in this region and excessive glottal and supraglottal compression [1, 2, 5]. …”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported complaints, such as hoarseness, throat irritation, frequent choking, pain in the neck and cervical region, discomfort when speaking, and vocal fatigue [8-10]. In perceptual-auditory and acoustic assessments, studies have described the presence of hoarseness, breathiness, roughness, vocal strain, hard glottal attack, laryngopharyngeal resonance, and fundamental frequency (F 0 ), jitter, and shimmer above normal levels [1, 4, 9, 11]. In addition, there are reports of elevation and tension in the cervical region during inhaling movement, besides reduced maximum phonation times (MPTs) [12-14].…”
Section: Introductionmentioning
confidence: 99%